Aluminum-induced rapid changes in the microtubular cytoskeleton of tobacco cell lines - Schwarzerová, Katerina; Zelenková, Sylva; Nick, Peter; Opatrný, Zdenek (Plant & cell physiology, 2002)
Aluminum (Al) is a major factor that limits plant growth in acid soils. It causes a cessation of root growth and changes in root morphology suggesting a role of the root cytoskeleton as a target of Al-toxicity. Here we report a rapid effect of Al on the microtubular cytoskeleton of the suspension tobacco cell lines BY-2 and VBI-0. Viability studies showed that the cells were more sensitive to Al during exponential phase as compared to stationary cells. During the first hours of exposure, Al induced the formation of additional bundles of cortical microtubules (cMTs), whereas the thickness of the individual bundles decreased. Prolonged exposure resulted in disorientation of cMTs. These changes of cMTs preceded the decrease of cell viability by several hours and were accompanied by an increase in the levels of alpha-tubulin (in its tyrosinated form) and elements of the tubulin-folding chaperone CCT. These findings suggest that the microtubular cytoskeleton is one of the early targets of Al toxicity.
Keywords: Tubulin; Cytoskeleton; hliník; buněčné linie; Dinitrobenzenes; Microscopy, Fluorescence; mikrotubuly; Sulfanilamides; Aluminum; cytoskelet; Nicotiana; Tyrosine; sulfanilamidy; Chaperonins; fluorescenční mikroskopie; Immunoblotting; dinitrobenzeny; Cell Line; chaperoniny; tubulin; tyrosin; Microtubules; imunoblotting; Cell Survival; viabilita buněk; tabák